2022
DOI: 10.1177/20543581211066720
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative and Qualitative Study on Patient and Physician Perceptions of Nephrology Telephone Consultation During COVID-19

Abstract: Background: COVID-19 required rapid adoption of virtual modalities to provide care for patients with a chronic disease. Care was initially provided by telephone, which has not been evaluated for its effectiveness by patients and providers. This study reports patients’ and nephrologists’ perceptions and preferences surrounding telephone consultation in a chronic kidney disease (CKD) clinic. Objective: To evaluate patient and physician perspectives on the key advantages and disadvantages of telephone consultatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…This supports prior studies reporting that patients prefer to meet new providers in-person first to create a more comfortable rapport. 28 In addition, telemedicine offered providers a view into their patients' homes, lives, and families, which created more intimacy in the remote patient-provider relationship. A study by Gomez et al 18 highlighted the benefits of seeing patients' homes and families during the visits, which was confirmed in our study by both providers and patients, even though some also expressed concerns around privacy.…”
Section: Discussionmentioning
confidence: 99%
“…This supports prior studies reporting that patients prefer to meet new providers in-person first to create a more comfortable rapport. 28 In addition, telemedicine offered providers a view into their patients' homes, lives, and families, which created more intimacy in the remote patient-provider relationship. A study by Gomez et al 18 highlighted the benefits of seeing patients' homes and families during the visits, which was confirmed in our study by both providers and patients, even though some also expressed concerns around privacy.…”
Section: Discussionmentioning
confidence: 99%
“…A survey among nephrologists reported increased access for patients, but concerns with proper physical examination, monitoring, and education of patients. They also reported less job satisfaction and sense of connection with patients [ 32 ]. Many studies focused on family physicians and generally, primary care clinicians have found virtual care acceptable, improves access and quality of care [ 33 - 36 ], and provides them with flexibility [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients reported a similar quality of care with telephone medication reviews compared to in-person reviews and found them to be convenient and effective. These findings are supported by a survey of 235 non-dialysis CKD patients from Ontario, Canada, who were converted from in-person to telephone visits with their nephrologist in response to the COVID-19 pandemic [ 19 ]. In our study, patients were very comfortable with telephone consultation and felt their concerns and preferences were addressed equally well compared with in-person visits.…”
Section: Discussionmentioning
confidence: 76%